Nonconservative recombination in Escherichia coli. - Takahashi, N K (1992)
Homologous recombination between two duplex DNA molecules might result in two duplex DNA molecules (conservative) or, alternatively, it might result in only one recombinant duplex DNA molecule (nonconservative). Here we present evidence that the mode of homologous recombination is nonconservative in an Escherichia coli strain with an active RecF pathway (a recBC sbcBC mutant). We employed plasmid substrates that enable us to recover both recombination products. These plasmids carry two mutant alleles of neo gene in direct orientation, two drug-resistance marker genes, and two compatible replication origins. After their transfer to the cells followed by immediate selection for the recombination to neo+, we could recover only one recombination product. A double-strand break at the region of homology increased this nonconservative recombination. If a nonconservative exchange should leave an end, this end may stimulate another exchange. Such "successive half crossing-over events" can explain several recombination-related phenomena in E. coli, including the origin of plasmid linear multimers and of transcribable, nonreplicated recombination products, and also in yeast and mammalian cells.